Implementation of platooning strategy for autonomous mobile robot - Baarath, Kunjunni (2016)
Current studies show automated mobile robot is being widely researched to reduce human work and ease the job. Hazards and human limitations have been the main reason for the demand for a more versatile and robust mobile robot especially in machining industries and military base. However, still often require this kind of robot as assisting equipment in public places such as shopping mall, airport to help senior citizens and disabled people who are unable to carrying things with them when they move around. In this project, an automated mobile robot was developed perpendicularly with proposing platooning system to be used. The model of the platooning strategy analyzed via simulation and experiments. The robot was built together with myRIO as main controller. The Kinect was used for human detection and acquiring distance data. MATLAB was used as interface to send the distance data from the Kinect to myRIO using UDP. Results found that the automated mobile robot successfully detect and follow human to the target location while carrying some objects. It is believed that this robot can reduce the burden of human especially senior citizen and disabled people when carrying heavy things in public places. Moreover, this robot also can contribute more in completing heavy task in human daily life.